Clinical characteristics and prevalence of angina in coronary patients treated at cardiology outpatient clinics in the city of Cascavel, Paraná (Research, Society and Development, 2023)
Introduction: Coronary artery disease affects thousands of individuals worldwide and is one of the leading causes of death in both developed and developing countries. Its significance is substantial, as nearly half of the patients affected by acute coronary syndrome do not even make it to the hospital. Objectives: To analyze the clinical profile of individuals with coronary artery disease and the prevalence of angina in this population in the city of Cascavel, Paraná. Methodology: This is a quali-quantitative study in which medical records were evaluated to establish previous and current comorbidities, the presence or absence of previous acute ischemic events, and the occurrence of angina in patients receiving outpatient care. Results: There was a predominance of individuals aged 60 to 74 years (n = 91; 60.7%) and males (n = 105; 70%). Regarding the presence of angina, 31.3% (n = 47) reported experiencing angina. Among the comorbidities presented, 40.7% (n = 61) had diabetes mellitus. Additionally, 14.7% (n = 22) were obese, 72.7% (n = 109) had dyslipidemia, and 92% (n = 138) were hypertensive. Bi-arterial disease occurred in 29.3% (n = 44) and tri-arterial disease in 28.7% (n = 43). Discussion: Among the risk factors, the most frequent were systemic arterial hypertension, dyslipidemia, diabetes mellitus, and a previous myocardial infarction episode. Conclusions: These results highlight the importance of rigorous monitoring and preventive strategies in this population to reduce the impact of cardiovascular disease.